INTEGRASI SHIFA AL-QUR'AN DAN HERBAL DALAM KONSELING PSIKOTERAPI TABIB HASAN DI BENGKULU - Perdiansyah, Muhammad (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2025)
This study examines the practice of Tabib Hasan in Kaur Regency, Bengkulu, which integrates Shifa Al-Qur’an (the use of Quranic verses for healing) and herbal medicine in psychotherapy counseling. The background of this research is the limited access to mental health services in Indonesia, particularly in rural areas, and the need for a holistic approach. The research objectives include analyzing the profile of counseling problems, identifying the Quranic verses and herbs used, describing the integration process, evaluating the therapy outcomes, and developing a conceptual framework for Islamic psychotherapy counseling. A qualitative descriptive method with a case study and phenomenological approach was employed, involving in-depth interviews, participatory observation, and documentation. The results show that Tabib Hasan primarily addresses physical complaints triggered by stress, using specific Quranic verses and various herbs. The therapy process includes holistic assessment and spiritual counseling sessions, with clients reporting improved sleep quality and calmness. Therapy success is measured by the client's awareness of their improved condition. This research presents an innovation through the holistic integration of Shifa Al-Qur’an and herbal medicine, and the development of a conceptual framework for Islamic psychotherapy counseling. Keywords: psychotherapy counseling, shifa al-qur’an, herbal medicine.